The Effect of Women's Perceptions on Women's Participation in Mangrove Conservation Supervised by CarbonEthics Foundation in Dompak Island, Riau Island Province, Indonesia - Novi Gabriella Haria; Siti Arieta; Sadam Sadam (Badan Perencanaan, Penelitian dan Pengembangan Pemerintah Provinsi Kepulauan Riau, 2022)
Women's participation in mangrove conservation is very influential in reducing the effects of greenhouse gases that cause climate change. How much women's participation is driven by women's perceptions of mangrove conservation. The purpose of this study was to determine the perceptions and forms of women's participation in mangrove conservation on Dompak Island, Riau Archipelago. This study used quantitative methods with the help of questionnaires and interviews with selected informants based on purposive sampling method. The results showed that women's perceptions of mangrove conservation were very good and the level of women's participation in mangrove conservation was good.